Integrative taxonomy reveals a new species of freshwater mussel, Potamilus streckersoni sp. nov. (Bivalvia: Unionidae): implications for conservation and management. Issue 4 (19th May 2019) - Smith, Chase H.; Johnson, Nathan A.; Inoue, Kentaro; Doyle, Robert D.; Randklev, Charles R.
Abstract : Inaccurate systematics confound our ability to determine evolutionary processes that have led to the diversification of many taxa. The North American freshwater mussel tribe Lampsilini is one of the better-studied groups in Unionidae, however, many supraspecific relationships between lampsiline genera remain unresolved. Two genera previously hypothesized to be non-monophyletic that have been largely overlooked are Leptodea and Potamilus . We set out to resolve supraspecific relationships in Lampsilini and test the monophyly of Leptodea and Potamilus by integrating molecular, morphological, and life history data. Our molecular matrix consisted of four loci: cytochrome c oxidase subunit 1 (CO1), NADH dehydrogenase subunit 1 (ND1), internal transcribed spacer 1 (ITS1), and 28S ribosomal RNA . Secondly, we performed both traditional and Fourier shape morphometric analyses to evaluate morphological differences and finally, we compared our results with available life history data. Molecular data supported the paraphyly of both Leptodea and Potamilus, but nodal support was insufficient to make any conclusions regarding generic-level assignments at this time. In contrast, inference from our integrative taxonomic assessment depicts significant support for the recognition of a new species, Potamilus streckersoni sp. nov., the Brazos Heelsplitter. Our data show clear separation of three taxonomic entities in the P. ohiensis species complex: P. amphichaenus, P. ohiensis, and P. streckersoni sp. nov.; all molecularly, geographically, and morphologically diagnosable. Our findings have profound implications for unionid taxonomy and will aid stakeholders in establishing effective conservation and management strategies.http://www.zoobank.org/urn:lsid:zoobank.org:pub:502647C0-418B-4CC4-85A8-BD89FC3F674F